(3GdceGd aj GdaQhSjI hCfhGY GdSdGMs
(3ChdgG (B:s
(3EHJOGA GdQchH hJYdje GdaQhSjI GdMeO ddg Pi GdYXeI hGdSdWGf abGd (B( (3jG CjgG GdPjf BefhG bGJdhG GdPjf jdhfce ef GdcaGQ hdjLOhG ajce ZdXI hGYdehG Cf Gddg eY GdeJbjf (B) s
(3BNQgG (B:s
(3hGdedGe hgh Ohf Pdc ai GdUaI hgh LjO hGdeUQhQI hgh GdeSJOjQ ef GdMhGaQ hGddg CYde s
(3HQSe NRGfI GdSdWGf Gdedc GdCTQa CHj GdfUQ bGfUhIs
(3HgG fXGe GdJYbjHIs
(3fSNI NRGFfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs